“Debriefing and Organizational Lessons Learned” (DOLL): A Qualitative Study to Develop a Classification Framework for Reporting Clinical Debriefing Results - Paquay, Méryl; Dubois, Nadège; Diep, Anh Nguyet; Graas, Gwennaëlle; Sassel, Tamara; Piazza, Justine; Servotte, Jean-Christophe; Ghuysen, Alexandre (Frontiers in Medicine, 2022)
Background The COVID-19 crisis has radically affected our healthcare institutions. Debriefings in clinical settings provide a time for the clinicians to reflect on the successes (pluses) and difficulties (deltas) encountered. Debriefings tend to be well-received if included in the broader management of the unit. The goal of this study was to develop a framework to categorize these debriefings and to assess its worthiness. Methods A qualitative approach based on a grounded theory research method was adopted resulting in the “Debriefing and Organizational Lessons Learned” (DOLL) framework. Debriefings were conducted within two Emergency Departments of a Belgian University Hospital during an 8-week period. In the first step, three researchers used debriefing transcripts to inductively develop a tentative framework. During the second step, these three researchers conducted independent categorizations of the debriefings using the developed framework. In step 3, the team analyzed the data to understand the utility of the framework. Chi-square was conducted to examine the associations between the item types (pluses and deltas) and the framework's dimensions. Results The DOLL is composed of seven dimensions and 13 subdimensions. Applied to 163 debriefings, the model identified 339 items, including 97 pluses and 242 deltas. Results revealed that there was an association between the frequency of pluses and deltas and the dimensions (p < 0.001). The deltas were mainly related to the work environment (equipment and maintenance) (p < 0.001) while the pluses identified tended to be related to the organization of the unit (communication and roles) (p < 0.001). With leadership's support and subsequent actions, clinicians were more enthusiastic about participating and the researchers anecdotally detected a switch toward a more positive organizational learning approach. Conclusion The framework increases the potential value of clinical debriefings because it organizes results into actionable areas. Indeed, leadership found the DOLL to be a useful management tool. Further research is needed to investigate how DOLL may work in non-crisis circumstances and further apply the DOLL into incident reporting and risk management process of the unit.